Longitudinal change and prognostic significance of serum PINK1 levels, and mediation role of delayed cerebral ischemia in human aneurysmal subarachnoid hemorrhage: an observational analytical study - He, Guo-Jun; Xie, Feng-Ju; He, Fei-Long; Ni, Wei-Fang; Chen, Si-Hua; Wang, Gang (Frontiers in Neurology, 2025)
BackgroundPTEN-induced putative kinase 1 (PINK1) is an endogenous protective protein. This study analyzed the prognostic implications of serum PINK1 levels and assessed the mediation effect of delayed cerebral ischemia (DCI) in human aneurysmal subarachnoid hemorrhage (aSAH).MethodsIn this observational analytical study of 201 aSAH patients and 87 healthy controls, serum PINK1 levels were measured at admission of all patients, from admission up to day 14 in 87 of all patients and at study entry in controls. The modified Fisher scale (mFisher) and World Federation of Neurological Surgeons scale (WFNS) were recorded for reflecting severity, and in-hospital DCI and post-aSAH 90-day Glasgow Outcome Scale (GOS) were documented as the two outcome variables.ResultsSerum PINK1 levels of patients were sharply increased at admission, and were still higher until day 14 than those of controls. Admission serum PINK1 levels were independently correlated with WFNS scores and mFisher scores, were linearly related to probabilities of DCI and poor prognosis, were independently associated with continuous GOS scores, ordinal GOS scores, DCI, and poor prognosis, and efficiently distinguished risks of DCI and poor prognosis under the receiver operating characteristic curve. The models of DCI and poor prognosis, encompassing their respective independent predictors, performed well. The association between admission serum PINK1 level and poor prognosis was partially mediated by DCI.ConclusionA notable elevation in serum PINK1 levels after aSAH is strongly related to illness severity, worse 90-day prognosis, and DCI, and DCI may in part navigate the links between serum PINK1 levels and poor prognosis following aSAH.